(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a bibliometric study analyzing trends in the academic literature at the intersection of technology skills, certifications, and careers. A dataset of publications from Scopus was examined using quantitative techniques including citation analysis, content analysis, topic modeling, and network analysis. The aim was to elucidate publication, citation, collaboration, and content patterns within this emerging domain. The citation analysis identified highly cited contributions and productive scholars. Content analysis uncovered frequently occurring keywords and underlying topics using computational methods such as latent Dirichlet allocation. Network analysis maps co-authorship links to assess collaborative dynamics. The results revealed a discernible upward trend in annual publications, indicating increasing research activity. However, citations are concentrated in a minority of published works and authors. “Skills,” “technology,” and “career” emerged as dominant keywords, validating alignment with the focus areas. Leading topics included education technology, skill development, and digital business. Co-authorship networks exhibit a well-connected multidisciplinary structure that spans diverse fields. The findings provide data-driven insights into the knowledge landscape at the intersection of technology skills, certifications, and careers. This initial bibliometric study establishes a quantitative baseline delineating key patterns in research output, influence, content, and collaboration. Multi-faceted analysis provides a foundation for guiding future scholarships. The limitations include reliance solely on Scopus and analyzing only publication data without other qualitative inputs. However, this study makes a useful contribution to the first empirical bibliometric investigation of these interlinked research domains. The findings can inform theory building, knowledge synthesis, and identification of underexplored aspects, warranting further research.